معاصر اجارہ میں دفع ِ ضرر اورتلفیق بین المذاہب کی فعالیت ہیئۃ المحاسبۃ والمراجعۃ کے فتاوی کا تحقیقی جائزہ - Abdul Razzaq; Muhammad Ijaz (Pakistan Journal of Islamic Research, 2019)
Talfiq is largely being used by Mujtahidin to solve the contemporary issues. Literally, It means to merge and put something together. However, In Islamic jurisprudence it is defined as "to follow opinion of more than one scholar (Mujtahidin), in a single matter of several branches and sub issues. Talfiq is allowed in matters which can be subject of probable Ijtihad and not allowed in believes and unanimous matters. Provided that, Talfiq leads to support of fundamental standards of Shariah and realization of valid interest of the people. Today, in tha age of globalization, Talfiq has gained more attention by contemporary Islamic scholars. They commonly use it while analyzing modern Issues, especially financial transactions to take interpretative judgment in the light of Islamic law. An apparent example of Talfiq application is Fatawa and standards issued by AAOIFI (Accounting and Auditing Organization of Islamic Financial Institutions). Ijara (Leasing) is one of those standards used in this regard. In Islamic law Ijara means "to give something on rent". It derives legitimacy from Quran and Sunnah. However, validity of many other products of Ijara based on the concept of Talfiq, i.e. 'Ijara muntahiya bit tamlik'. It is a contract of leasing with promise to sell. It is introduced by AAOIFI as an Islamic financing tool alternative to the interest-bearing hire purchase. The main cause of adopting Talfiq tool in Ijarah contract is 'hardship removal' that is important principle of shariah. This paper discusses in detail, the process of Talfiq applied in modern Ijarah cases.